Relativistic Quantum Scalar Fields (Bulletin of Pure and Applied Sciences – Physics, 2021)
A new equation for the relativistic scalar field is derived from the correspondence with the  classical commutator and covariance. It has the same form as the Klein Gordon equation with  different coefficients.